Новітні аудіовізуальні інструменти репрезентації української ідентичності на відеохостингах в умовах російсько-української війни - Мусієнко, Ольга Вячеславівна (My University, 2022)
The purpose of the article is to determine the main themes and directions of audiovisual representation of Ukrainian identity in the works on video hosting in the conditions of the Russian-Ukrainian war. The methodology. We conducted a qualitative content analysis of the works of the video hosting sites TikTok and YouTube according to the most popular Ukrainian studies tags and geographic queries. The results of the case were compared with the data obtained by the us during the studying other researchers on the topic. The results. Video hosting is defined as global informational and cultural carrier that increasingly actively promotes social and political trends. It was established that, unlike traditional media, video hosting broadcasts Ukrainian identity as a modern cultural and artistic trend. Video flash mobs (TikTok) and shorts (YouTube) became the main means of spreading Ukrainian identity. It was shown that the events of the Russian-Ukrainian war became a catalyst for national and political identity and a powerful social and cultural demand for Ukrainian art in the world.
Keywords: російсько-українська війна; відеохостинг; YouTube; TikTok; українська ідентичність; Russian-Ukrainian war; video hosting; Ukrainian identity